2016
DOI: 10.1007/s00247-016-3637-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing native liver fibrosis and esophageal varices using liver and spleen stiffness measurements in biliary atresia: a pilot study

Abstract: Liver and spleen stiffness measurements using ARFI imaging are potential noninvasive markers for liver fibrosis and esophageal varices in patients treated for biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…The study by Tomita H. et al found that liver stiffness measurements exhibited good predictive value for oesophageal varices, with a high AUC (0.90), while spleen stiffness measurements failed to predict oesophageal varices. 20 In contrast, the research by Zhang et al demonstrated that spleen stiffness measured by ARFI predicted oesophageal varices with an AUC of 0.81 and that liver stiffness measurements failed to predict oesophageal varices. 21 Many confounding factors, such as small sample sizes, may have led to contradictory conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…The study by Tomita H. et al found that liver stiffness measurements exhibited good predictive value for oesophageal varices, with a high AUC (0.90), while spleen stiffness measurements failed to predict oesophageal varices. 20 In contrast, the research by Zhang et al demonstrated that spleen stiffness measured by ARFI predicted oesophageal varices with an AUC of 0.81 and that liver stiffness measurements failed to predict oesophageal varices. 21 Many confounding factors, such as small sample sizes, may have led to contradictory conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Ultrasound (US) elastography is a non-invasive, quantitative, and accurate diagnostic technique that can identify liver fibrosis without biopsy in various chronic liver diseases (6,7). A few studies have reported the promising diagnostic efficacy of US elastography techniques in patients with postoperative BA by using two-dimensional shear wave elastography (2D-SWE), acoustic radiation force impulse (ARFI) imaging, and transient elastography (TE) (8)(9)(10). However, no reports have documented attempts to compare the diagnostic accuracy of 2D-SWE and TE in BA.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,20 The patient populations varied among the included studies, including 4 reports with patients who had various chronic or suspected liver diseases, 11,15,19,20 3 studies with cystic fibrosis cohorts, 10,16,17 and 4 studies with patients who had biliary atresia. [12][13][14]18 The age range of the patients in the 11 included studies was 3 months to 25 years. Table 2 summarizes the technical characteristics of the US elastographic procedures in the included studies.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%